Predicting College Students’ Adoption of Technology for Self-Directed Learning: A Model Based on the Theory of Planned Behavior With Self-Evaluation as an Intermediate Variable - Tzeng, Sy-Yi; Lin, Kuen-Yi; Lee, Chih-Yu (Frontiers in Psychology, 2022)
Many studies assume a significant relationship between intention and behavior. However, the data do not always support this assumption (e.g., Agudo-Peregrina, Hernandez-Garcia, & Pascual-Miguel, 2014). This study used a modified version of social cognitive theory with self-evaluations as an intermediate variable to explore and resolve the problems associated with applying the theory of planned behavior to explain students’ adoption of technology for self-directed learning. We surveyed 285 college students who enrolled in an e-book publishing course using multifaceted technological learning tools. We found that, as an intermediate variable, self-evaluation enhanced the influence of intentions on behavior and improved the accuracy of predictions of college students’ adoption of technology for self-directed learning. Students’ attitudes and perceived behavioral control were important factors influencing their adoption of technology for self-directed learning through their effects on intention; subjective norms were not important in this respect.